MEDU-20. HDAC AND NFκB ANTAGONISTS SYNERGISTICALLY INHIBIT GROWTH OF MYC-DRIVEN MEDULLOBLASTOMA. (23rd April 2019) - Marquardt, Viktoria; Theruvath, Johanna; Pauck, David; Picard, Daniel; Qin, Nan; Blümel, Lena; Hansen, Finn K; Felsberg, Jörg; Cheshier, Samuel; Reifenberger, Guido; Borkhardt, Arndt; Kurz, Thomas; et al.
Abstract: Medulloblastoma is the most common malignant brain tumor in childhood and comprises four distinct molecular subgroups with further layers of intertumoral heterogeneity. Amplification of the oncogene MYC drives tumorigenesis and constitutes a hallmark feature underlying Group 3 biology. Metastatic dissemination is frequently observed at diagnosis or recurrence and confers a dismal prognosis. Employing our in-house drug screening pipeline, we evaluated a library of epigenetic inhibitors (n=78) in various brain tumor cell lines including glioblastoma (n=14), medulloblastoma (n=14) and atypical teratoid/rhabdoid tumors (n=11). By this cross-entity approach we revealed preferential activity of histone deacetylase inhibitors (HDACi) in MYC-driven medulloblastoma. In a secondary HDACi (n=20) screen, we identified the clinically established, class I selective HDACi CI-994 as the compound with the most preferential antitumoral effect in MYC-driven medulloblastoma. We confirmed that the inhibitor response was in part MYC-dependent as our lentiviral based MYC-overexpression model showed higher sensitivity towards CI-994 treatment as compared to the isogenic control with low endogenous MYC expression. Moreover, we observed significantly reduced MYC mRNA and protein expression levels, decreased cell viability and induction of apoptosis following CI-994 treatment. Notably, CI-994 showed significant antitumoral effects at the primary site and the metastatic compartment in two orthotopic mouse models of MYC-driven medulloblastoma. Additionally, a screen for synergistic drug interaction with a clinical inhibitor library of approved chemotherapeutics and clinical phase III/IV agents (n=199) revealed a favorable interaction of the NFκB inhibitor bardoxolone methyl with CI-994. In line with our synergy data, RNA sequencing profiling confirmed the functional relevance of NFκB pathway induction upon CI-994 treatment. In all, our pharmacogenomic approach suggests that the combination with NFκB inhibitors has the potential to increase the anitumoral activity of HDACi and the pronounced activity in MYC amplified medulloblastoma, where therapeutic options are limited, is particular noteworthy and warrants further clinical investigation.